Diffusion‐weighted MR imaging increases diagnostic accuracy of breast MR imaging for predicting axillary metastases in breast cancer patients. Issue 1 (16th November 2018) - Guvenc, Inanc; Whitman, Gary J.; Liu, Ping; Yalniz, Ceren; Ma, Jingfei; Dogan, Basak E.
Abstract: Purpose: To evaluate the incremental value of diffusion‐weighted imaging (DWI) to conventional MR imaging (CMRI) to predict ipsilateral metastatic axillary lymphadenopathy in patients with newly diagnosed breast cancer. Subjects and methods: In an IRB approved retrospective single‐institution study, newly diagnosed consecutive breast cancer patients with pathological verification of axillary lymph node (LN) status who had undergone breast MR imaging, including DWI as part of their standard MRI between August 1, 2010, and December 31, 2010, were reviewed. Lesion size, tumor grade, and tissue prognostic factors were noted. Ipsilateral axillary LNs were evaluated using morphological criteria on CMRI. Apparent diffusion coefficient (ADC) values of suspicious ipsilateral LNs were obtained and compared with ADC values of contralateral benign axillary LNs. Receiver operating characteristic curves and multivariate logistic regression analyses were used using pathology as the gold standard. Results: Eighty‐five eligible patients were identified, with surgical pathology revealing 34 patients (40%) who had malignant and 51 (60%) had benign ipsilateral axillae. The sensitivity of CMRI was 79%, with a specificity of 81%, a positive predictive value (PPV) of 65%, and a negative predictive value (NPV) of 89%. On DWI, the mean ADC value was significantly lower for metastatic LNs (0.89 ± 0.18 × 10 −3 mm 2 /s) than for benign ipsilateral LNs (1.41 ± 0.21 × 10 −3 mm 2 /s; P < 0.0001). Using a cutoff ADC value of 0.985 × 10 −3 mm 2 /s, yielded improved sensitivity, specificity, PPV, and NPV of 83%, 98%, 95%, and 93%, respectively. Conclusion: Apparent diffusion coefficient values increase the specificity of CMRI for predicting ipsilateral axillary LN metastases in patients with newly diagnosed breast cancer.